Can a brief peer-led group training intervention improve health literacy in persons living with HIV? Results from a randomized controlled trial. Issue 5 (May 2021) - Sanders, Mechelle; Tobin, Jonathan N.; Cassells, Andrea; Carroll, Jennifer; Holder, Tameir; Thomas, Marie; Luque, Amneris; Fiscella, Kevin
Highlights: eHealth literacy and HIV health literacy increased in the intervention group. The greatest improvements were among those with the lowest health literacy scores. Our findings have implications for broadening the function of peers/lay health workers in the health care continuum. Abstract: Objective: The goal of this study was to determine if a 6-week, peer-led intervention improves health literacy and numeracy among people living with HIV (PLWH). Methods: We used a randomized controlled trial with repeated measurements, which included six, 90-minute, group-based training sessions. We recruited PLWH participants (n = 359) from safety-net practices in the New York City Metropolitan area and Rochester, NY. Participants were randomly assigned (1:1) to an intervention group (n = 180) or a control group (n = 179). Outcome measures were collected at baseline, eight weeks post-baseline, and at six months using the Brief Estimate of Health Knowledge and Action-HIV (BEHKA-HIV), the Electronic Health Literacy Scale (eHEALS), the Rapid Estimate of Adult Literacy (REALM), and the Newest Vital Sign (NVS). Results: The intervention group had statistically significant improvements in eHealth literacy and BEHKA-HIV compared to the control group. There were no statistically significant changes in general health literacy or numeracy in either group. The intervention had the greatest impact on participants with the lowest levels of eHealth literacy at baseline. Conclusion: The intervention had a positive impact on participants' HIV health literacy and eHealth literacy. Practice implications: Our findings have implications for broadening the function of peer-workers in the health care continuum.